Perspectives on COVID-19 testing policies and practices: a qualitative study with scientific advisors and NHS health care workers in England - Anne-Marie Martindale; Caitlin Pilbeam; Hayley Mableson; Sarah Tonkin-Crine; Paul Atkinson; Aleksandra Borek; Suzannah Lant; Nina Gobat; Tom Solomon; Sally Sheard (BMC, 2021)
Abstract Background As COVID-19 death rates have risen and health-care systems have experienced increased demand, national testing strategies have come under scrutiny. Utilising qualitative interview data from a larger COVID-19 study, this paper provides insights into influences on and the enactment of national COVID-19 testing strategies for health care workers (HCWs) in English NHS settings during wave one of the COVID-19 pandemic (March-August 2020). Through the findings we aim to inform learning about COVID-19 testing policies and practices; and to inform future pandemic diagnostic preparedness. Methods A remote qualitative, semi-structured longitudinal interview method was employed with a purposive snowball sample of senior scientific advisors to the UK Government on COVID-19, and HCWs employed in NHS primary and secondary health care settings in England. Twenty-four interviews from 13 participants were selected from the larger project dataset using a key term search, as not all of the transcripts contained references to testing. Framework analysis was informed by the non-adoption, abandonment, scale-up, spread, and sustainability of patient-facing health and care technologies implementation framework (NASSS) and by normalisation process theory (NPT). Results Our account highlights tensions between the communication and implementation of national testing developments; scientific advisor and HCW perceptions about infectiousness; and uncertainties about the responsibility for testing and its implications at the local level. Conclusions Consideration must be given to the implications of mass NHS staff testing, including the accuracy of information communicated to HCWs; how HCWs interpret, manage, and act on testing guidance; and the influence these have on health care organisations and services.